The Belt and Road Initiative in Malaysia: Progress, Impacts and Challenges - Abdullah, Zaharul; Said, Noor Ashikin; Muhamad, Rosyidah (INTERNATIONAL JOURNAL OF CHINA STUDIES, 2025)
The Belt and Road Initiative (BRI), launched by China in 2013, is an extensive infrastructure programme aimed at enhancing connectivity in areas such as policy coordination, infrastructure, trade, finance and peopleto-people relations. Among Southeast Asian countries, Malaysia, particularly during the tenure of former Prime Minister Najib Razak, demonstrated strong support for the BRI. Various projects have been implemented across multiple sectors, including infrastructure development, energy, industrial parks, construction, real estate, telecommunications, technology, finance, banking and tourism. However, when Mahathir Mohamad returned to power in 2018, he adopted a more cautious stance towards Chinese investments, opting to review and renegotiate key BRI projects to ease Malaysia’s financial strain. The administrations of Muhyiddin Yassin and Ismail Sabri focused primarily on handling the COVID-19 pandemic and economic recovery, allowing most BRI projects to continue without interruption, a trend that has persisted under Prime Minister Anwar Ibrahim. Although Malaysia’s overall approach to China remains consistent, the country’s frequent changes in government—four administrations in five years—have resulted in varied responses and shifting priorities regarding BRI projects. This study examines the progress, impacts and challenges of these projects. The findings reveal that most BRI projects in Malaysia are advancing smoothly despite political changes. Impacts range from high costs toconcerns over autonomy and policy space, while challenges include reducing dependence on China and increasing diversification to maintain active neutrality.